Enhanced Capacitive Deionization Exploiting Novel Functionalized Graphene Oxide Electrodes. Issue 8 (9th March 2022) - Pedico, Alessandro; Bocchini, Sergio; Tresso, Elena; Lamberti, Andrea
Abstract: In this study, a novel functionalized graphene oxide (fGO) is proposed for application in water desalination. The fGO is obtained with a simple and scalable method. Pristine GO is functionalized with (2‐(acryloyloxy)ethyl)trimethylammonium through a two‐step functionalization. Then, it is mixed with activated carbon and coated onto a metallic current collector. Material characterization techniques such as electron microscopy, thermal analyses, and infrared spectroscopy are employed to study the physical and chemical structures of the proposed materials. This process provides a porous electrode useful for capacitive deionization (CDI). The desalination performance is compared to the performance of bare activated carbons, showing a remarkable improvement. The final device reaches a value of around 17 mg g ‐1 of salt removal, with a charge efficiency of 98%. The findings from this study lay the groundwork for future research, contributing in increasing the existing knowledge on materials for CDI. Abstract : A novel functionalized graphene oxide (fGO) is proposed for water desalination. The fGO is obtained with a simple, scalable method. The fGO is mixed with activated carbon to obtain porous electrodes for capacitive deionization. The desalination performance shows a remarkable improvement compared to activated carbon. A salt removal of 17 mg g −1 and a charge efficiency of 98% are achieved.